PENGARUH TINGKAT KOMPETENSI KOMUNIKASI INTERPERSONAL DAN KUALITAS PELAYANAN TENAGA KESEHATAN TERHADAP TINGKAT KEPUASAN PASIEN BPJS KESEHATAN DI KOTA SEMARANG - Rona Arinal Haq; Triyono Lukmantoro; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
As many as ten hospitals in Semarang City are suspected of neglecting patients using BPJS Health. The initial survey was conducted to obtain supporting data. Conducting interviews using a questionnaire sheet to 30 BPJS Health patients who have or are currently receiving hospital’s services. There are three cases of BPJS Health patients who were rejected by the hospital. The purpose of this study was to determine the effect of Interpersonal Communication Competency Level and Service Quality of Health Workers on BPJS Health Patients Satisfaction Levels in Semarang City. The theory used in this research is interpersonal need gratification theory and the expectancy disconfirmation model. The method used is a quantitative approach using a simple random sampling technique, with a total of 155 respondents who are BPJS Health patients at X Hospital in July 2022. The results of the first hypothesis test indicate that there is an effect of the level of interpersonal communication competence of health workers on the satisfaction level of BPJS Health patients with a significance value is 0.000. The results of the second hypothesis test indicate that there is an effect of the quality of health services on the satisfaction level of BPJS Health patients with a significance value is 0.000.